The Relationship between Narcissism, Perfectionism, and Parenting Styles: The Mediating Role of Coping Styles - Nouri, Zahra; Haghi Nashrodkoli, Roqaye; Habibzadeh, Kimia (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The purpose of the current research was to investigate the relationship between narcissism, perfectionism, and parenting styles, and the mediating role of coping styles in this relationship. Methods and Materials: This study was descriptive-correlational and conducted using structural equation modeling (SEM). The population of this research consisted of Iranian men and women, with 250 individuals analyzed as the primary sample. Data collection was carried out through convenience sampling using questionnaire links. The instruments used in this study included the Narcissistic Personality Inventory (Raskin & Hall, 1979), the Baumrind Parenting Styles Questionnaire (1971), the Perfectionism Questionnaire by Hill et al. (2004), and the Coping Styles Questionnaire by Carver, Scheier, and Weintraub (1989). Data analysis was performed using SPSS and AMOS statistical software. Findings: Findings indicate that authoritarian and permissive parenting styles are associated with higher levels of narcissism. Perfectionism, especially when it manifests negatively, is related to narcissism. Furthermore, coping styles act as mediators in these relationships, such that individuals with more positive coping styles are less prone to narcissism. Conclusion: This study can contribute to a better understanding of the relationships between parenting styles, perfectionism, and narcissism, and can be useful in designing therapeutic and preventive programs for individuals with narcissistic personality disorder. Additionally, the findings of this research can assist parents and professionals in avoiding parenting styles and coping methods that may contribute to the reinforcement of narcissism.